2019
DOI: 10.1007/s10237-019-01144-2
|View full text |Cite
|
Sign up to set email alerts
|

In silico approach to quantify nucleus self-deformation on micropillared substrates

Abstract: Considering the major role of confined cell migration in biological processes and diseases, such as embryogenesis or metastatic cancer, it has become increasingly important to design relevant experimental setups for in vitro studies. Microfluidic devices have recently presented great opportunities in their respect since they offer the possibility to study all the steps from a suspended to a spread, and eventually crawling cell or a cell with highly deformed nucleus. Here, we focus on the nucleus self-deformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…Once the cell approaches the substrate, the contact force f ct applies over a very thin layer corresponding to the intersection between the cell and the substrate. We have shown that f ct can be approximated by a volume force [26] and it can be computed via a penalization technique as follows:…”
Section: The Cell Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Once the cell approaches the substrate, the contact force f ct applies over a very thin layer corresponding to the intersection between the cell and the substrate. We have shown that f ct can be approximated by a volume force [26] and it can be computed via a penalization technique as follows:…”
Section: The Cell Environmentmentioning
confidence: 99%
“…The latter, which may be discrete [20][21][22] or continuum [15,[23][24][25], allows to investigate the intra-cellular rearrangement or to obtain quantitative results at the global or the local scale. In our previous paper [26], we have proposed an in silico two-dimensional (2D) model which simulates the first three steps (i.e., contact, adhesion and spreading) of the interaction between the cell and the micropillared substrate and provides insights on the mechanisms inducing nuclear deformation. We have been able to determine the role of the gravity and of the actin fibers above and beneath the nucleus responsible for a pushing and a pulling force, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation